Abnormal Sexual Behavior During Sleep in Temporal Lobe Epilepsy: a Case Report - Pelin, Zerrin; Yazla, Ece (My University, 2012)
Herein, we describe a case who presented with abnormal sexual behaviour during sleep. Video-electroencephalography monitoring during sleep revealed an abnormality suggesting an epileptic basis. The patient was successfully treated with carbamazepin. The psychiatric symptoms that were thought to be related to abnormal sexual behaviours were controlled with antipsychotic treatment. Our findings strongly emphasize the fact that efforts should be spent to increase awareness of seizure activity at night, which can be misinterpreted as benign parasomnias. Such a misinterpretation may have serious consequences, such as insufficient seizure control, progressive personality changes, and cognitive impairment.
Keywords: Sexual behaviour during sleep; nocturnal seizure; temporal lobe epilepsy; sexsomnia